Bi(nanoparticles)/CNx(nanosheets) nanocomposites as high capacity and stable electrode materials for supercapacitors: the role of urea. Issue 35 (28th July 2020) - Butenko, Denys S.; Zhang, Xinyu; Zatovsky, Igor V.; Fesych, Igor V.; Li, Shilin; Chen, Ruoyu; Chufarov, Marian; Symonenko, Oleksii; Klyui, N. I.; Han, Wei
Abstract : A facile method was developed to prepare Bi/CN x nanocomposites for high performance energy storage devices. Abstract : The evolution of high-performance and stable electrode materials for supercapacitors plays a vital role in the next generation of energy storage devices. In this work we present a simple method for preparing Bi(nanoparticles)/CN x (nanosheets) nanocomposites as electrode materials for supercapacitors, which were synthesized by thermally treating bismuth citrate and urea at 550–700 °C under an Ar atmosphere. According to physicochemical studies (XRD, SEM, TG-DTA, XPS, FTIR, and BET), a "smeared" bismuth formation or the formation of nanoparticles on the CN x surface of interwoven 2D-nanosheets at different calcination temperatures was observed. Electrochemical measurements show that the specific capacity of the composites can reach 1251 F g −1 (more than 90% of the theoretical value) at a current density of 500 mA g −1 in a 6 M KOH electrolyte, and most two-dimensional CN x -based nanostructures remain intact after multiple galvanostatic charge–discharge processes, which is promising for the development of highly efficient supercapacitors. A supercapacitor composed of Bi/CN x nanocomposites for the negative electrode and Ni-layered hydroxide for the positive electrode demonstrates a high energy density of 58 W h kg −1 with a power density of 800 W kg −1 accompanied by a good cycle life (the parameters decreased down to only 78% after 1000 charge–discharge cycles). Our current results indicate that the addition of urea not only determines the morphology of the composites, but also lays the foundation for the development of new types of nanocomposites for the power industry.